Identification and antibiotic resistance testing of Gram-negative rod-shaped bacteria in birds of paradise (Paradisaeidae sp.) - Parameshtya, Sadhira; Wijaya, Agus; Safika, Safika (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2024)
Antibiotic resistance represents a critical global health challenge, and is characterised by the loss of effectiveness of antibiotics against bacterial growth. This phenomenon complicates treatment options for infections, underscoring the need to understand bacterial resistance mechanisms, particularly in protected species such as birds of paradise. This study aimed to identify the bacterial species present in faecal samples from three different species of birds of paradise and evaluate the efficacy of various antibiotics against these bacteria. Samples were collected from Taman Mini Indonesia Indah (TMII) in East Jakarta. Using MacConkey Agar for bacterial isolation and subsequent identification through Gram staining and biochemical tests, this study identified Serratia sp., Klebsiella sp., and Citrobacter sp. Antibiotic susceptibility was assessed using the Kirby-Bauer disk diffusion method against seven antibiotics: erythromycin, gentamicin, oxytetracycline, cefotaxime, sulfamethoxazole, doxycycline, and nalidixic acid. These findings revealed that sulfamethoxazole was notably more effective than the other antibiotics tested, highlighting its potential for treating infections in birds of paradise.